CQ Interview: Chris Shaw on Ethical Issues in Biotechnology - Kushner, Thomasine (Cambridge quarterly of healthcare ethics, 2002)
Chris Shaw is the Chair of Biotechnology and Head of the Pharmaceutical Biotechnology Research Group at the University of Ulster in Northern Ireland. His concern for the unequal distribution of benefits has prompted him to take a leading role in developing partnership models for scientists doing research in underdeveloped countries.